2021
DOI: 10.1002/jmv.27485
|View full text |Cite
|
Sign up to set email alerts
|

Host factors and vaccine efficacy: Implications for COVID‐19 vaccines

Abstract: The efficacy of the vaccines varies between individuals and populations. The immunogenicity of the vaccine is influenced by various factors, including host factors. Previous studies have shown that host factors affect the effectiveness of vaccines, which may be true about COVID‐19 vaccines. In this review, we evaluate the possible association of host factors with vaccine efficacy with a special focus on COVID‐19 vaccines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 56 publications
0
41
0
Order By: Relevance
“…Key determinants of vaccine efficacy emerged following global COVID-19 vaccine rollout [ 4 ], including host factors (i.e. age, immunocompromised status), viral factors (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Key determinants of vaccine efficacy emerged following global COVID-19 vaccine rollout [ 4 ], including host factors (i.e. age, immunocompromised status), viral factors (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy and effectiveness of COVID-19 vaccines might be influenced by several factors, such as the emergence of viral variants able to evade the immune response, the decline of antibody levels over time, and some other intrinsic host factors [11][12][13][14] . In order to maintain long-term protection and to counteract the reduced ability of available vaccines of neutralizing emerging VOCs, a third booster dose of mRNA vaccine is strongly recommended, since it has proved to confer significantly greater protection [14][15][16][17] .…”
mentioning
confidence: 99%
“…Field data on health care workers 29 and NH residents 23 during the SARS-CoV-2 Alpha variant outbreak confirmed that such levels of RBD-IgG (1050 AU/mL and 993 AU/mL, respectively) correlate with COVID-19 protection. www.nature.com/scientificreports/ Vaccine response is influenced by various host factors, which also result in a heterogeneous vaccine response such as age, immunosuppression and prior infection 7,35 . However, prevention strategies could nonetheless be improved by the identification of poor vaccine responders among residents at risk of severe forms of illness.…”
Section: Discussionmentioning
confidence: 99%